Genotype-specific effects of Mecp2 loss-of-function on morphology of Layer V pyramidal neurons in heterozygous female Rett syndrome model mice - Rietveld, Leslie; Stuss, David P.; McPhee, David; Delaney, Kerry R. (Frontiers in Cellular Neuroscience, 2015)
Rett Syndrome (RTT) is a progressive neurological disorder primarily caused by mutations in the X-linked gene methyl-CpG-binding protein 2 (MECP2). The heterozygous female brain consists of mosaic of neurons containing both wildtype MeCP2 (MeCP2+) and mutant MeCP2 (MeCP2-). 3-dimensional morphological analysis was performed on individually genotyped layer V pyramidal neurons in the primary motor cortex of heterozygous (Mecp2+/-) and wild-type (Mecp2+/+) female mice (>6 mo.) from the Mecp2tm1.1Jae line. Comparing basal dendrite morphology, soma and nuclear size of MeCP2+ to MeCP2- neurons reveals a significant cell autonomous, genotype specific effect of Mecp2. MeCP2- neurons have 15% less total basal dendritic length, predominantly in the region 70-130 μm from the cell body and on average 3 fewer branch points, specifically loss in the 2nd and 3rd branch orders. Soma and nuclear areas of neurons of mice were analyzed across a range of ages (5-21 mo.) and X-chromosome inactivation (XCI) ratios (12-56%). On average, MeCP2- somata and nuclei were 15% and 13% smaller than MeCP2+ neurons respectively. In most respects branching morphology of neurons in wild-type brains (MeCP2 WT) was not distinguishable from MeCP2+ but somata and nuclei of MeCP2 WT neurons were larger than those of MeCP2+ neurons. These data reveal cell autonomous effects of Mecp2 mutation on dendritic morphology, but also suggest non-cell autonomous effects with respect to cell size. MeCP2+ and MeCP2- neuron sizes were not correlated with age, but were correlated with XCI ratio. Unexpectedly the MeCP2- neurons were smallest in brains where the XCI ratio was highly skewed towards MeCP2+, i.e. wild-type. This raises the possibility of cell non-autonomous effects that act through mechanisms other than globally secreted factors; perhaps competition for synaptic connections influences cell size and morphology in the genotypically mosaic brain of RTT model mice.